2020
DOI: 10.1007/s00415-020-10099-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychological consequences of COVID-19 pandemic in Italian MS patients: signs of resilience?

Abstract: Background Anxiety, depression and reduction of quality of life (QoL) are common in people with multiple sclerosis (pwMS). Fear of getting sick from COVID-19, government's lockdown and the imposed social distancing might have had an impact on psychological distress and QoL. Objectives The aim of our study was to investigate anxiety, depression and QoL changes in pwMS during SARS-CoV-2 outbreak and lockdown in Italy. Methods 67 pwMS with a previous (less than 6 months) neuropsychological evaluation before SARS-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 35 publications
5
68
2
5
Order By: Relevance
“…17 Furthermore, no differences were found on most domains of HRQoL and depressive symptoms during the COVID-19 period compared with before COVID-19 in Italian and Serbian patients with multiple sclerosis. 18,19 One study explained these results by their population being accustomed to experiencing (medical traumatic) stress, 18 not accounted for in this study. However, these factors may increase the risk of psychosocial problems in all families in pediatric oncology on the longer term, and should therefore be examined in future research and care.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…17 Furthermore, no differences were found on most domains of HRQoL and depressive symptoms during the COVID-19 period compared with before COVID-19 in Italian and Serbian patients with multiple sclerosis. 18,19 One study explained these results by their population being accustomed to experiencing (medical traumatic) stress, 18 not accounted for in this study. However, these factors may increase the risk of psychosocial problems in all families in pediatric oncology on the longer term, and should therefore be examined in future research and care.…”
Section: Discussionmentioning
confidence: 81%
“…The In line with our results, recently published longitudinal studies in clinical adult populations also found signs of psychosocial resilience during the COVID-19 period. [17][18][19] In women with breast cancer, small but significant improvements were found in HRQoL during the COVID-19 period compared with before COVID-19. 17 Furthermore, no differences were found on most domains of HRQoL and depressive symptoms during the COVID-19 period compared with before COVID-19 in Italian and Serbian patients with multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological distress observed in autoimmune arthritis seems to be shared with some chronic diseases, including cardiovascular diseases [50], asthma and COPD [51], cancer [52,53], and psychiatric disorders [44,54,55]; whereas patients with other chronic conditions, such as multiple sclerosis [56] and, surprisingly, patients with diabetes, do not seem to have particularly suffered from the negative psychological consequences of COVID-19-induced lockdown, even though, for diabetes patients, their levels of adherence to treatment and lifestyle habits were reported to be significantly reduced [57]. The reason for these discrepancies among chronic conditions is difficult to interpret and may be ascribed to differences in study populations, such as age (i.e., older in arthritis than in multiple sclerosis or type I diabetes), gender (i.e., predominance of the female gender in arthritis than in type I diabetes), but also on the illness itself, such as severe inflammatory joint pain, stiffness and, consequently, functional limitation pathognomonic of autoimmune arthritis, which are closely dependent on tight medical monitoring, and can quickly impact the psychological well-being of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge and at the moment of preparation of the current paper, studies exploring the psychological impact of the COVID-19 pandemic on patients with MS are still sparse. Those articles do not explore specifically the changes in patients' disease perceptions or expectations on psychological support ( 28 33 ). Moreover, none of these articles integrated quantitative and qualitative methods.…”
Section: Introductionmentioning
confidence: 99%